Review : Metabolit Sekunder pada Algae - Andi Nur Samsi Arafah; Rusmidin (Universitas Sulawesi Barat, 2021)
All organisms have the ability to defend their lives from environmental threats. this can be seen from the secondary metabolites it contains. Secondary metabolites are compounds produced by organisms. Secondary metabolites are also found in marine life. Algae is a biota that is often explored to obtain secondary metabolites and is a major component in modern pharmacy. The potential of algae includes antiviral, antioxidant, antibacterial, neuromodulatory, antifungal, deworming, anti-inflammatory, anticancer, and others. One of the secondary metabolites produced by Phaeophyceae or brown algae is phlorotannin which functions as an antioxidant. There are several methods of extracting it. Macroalgae has great potential as bioprospecting.